PENGARUH TERAPI FOOT MASSAGE TERHADAP TEKANAN DARAH PADA PASIEN LANSIA DENGAN HIPERTENSI DI RSD K.R.M.T WONGSONEGORO KOTA SEMARANG - Prastiwi, Fitria Hardiyanti; Sonhaji, Sonhaji (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background : The results of the 2018 Rikesdas data explain that the prevalence of hypertension is 34,1%, which is mostly suffered by the elderly group. Management of hypertension can be done in a non-pharmacological way, namely by applying foot massage therapy to lower blood pressure. Purpose : To determine the effect of applying foot massage therapy on blood pressure in elderly patients with hypertension at RSD K.R.M.T Wongsonegoro Semarang in 2024. Results : Research results on client 1 and client 2 after foot massage therapy was carried out of 15 minutes in 3 visits. In client 1, before the foot massage therapy, his blood pressure was 178/149 mmHg, after the foot massage therapy, his blood pressure dropped to 164/121 mmHg. In client 2, before the foot massage therapy was carried out, his blood pressure was 182/122 mmHg, after the foot massage therapy was carried out, his blood pressure decreased to 169/109 mmHg. Conclusion : The application of foot massage therapy is effective in reducing blood pressure in elderly people with hypertension massage therapy can help provide relaxation stimulation so that it can lower blood pressure. Suggestion : It is hoped that the client’s family will be able to carry out foot massage therapy to help lower blood pressure in elderly people with hypertension on a regular basis to get satisfactory results.